Peranan Pembinaan Kemitraan Usaha Terhadap Peningkatan Produktivitas Perusahaan Industri Kecil Di Bandar Lampung - Vitratin Vitratin (Jurnal Riset Akuntansi dan Manajemen Malahayati, 2017)
The purpose of this study is to determine the influence of business partnership coaching onincreasing productivity of small industry companies and other factors that affect productivity. Themethod used in this research is survey method and kuisoner with linear regression analysis usingSPSS. Based on the results of this study it can be concluded that 46.7% increase in businessproductivity is influenced by business coaching while the remaining 53.3% is influenced by otherfactors..